Motivators and Barriers to Physical Activity among Healthcare Providers in Karbala City - Al-Najafi, Waleed Khalid; Talal, Naeem Obaid; Alkelaby, Hamid Hussein; Ali, Rawnaq Abdulrazzaq; Abd Alridha , Taghreed; Nahidh, Haider Kamil (Karbala Journal of Medicine, 2024)
Background: Physical inactivity is a major risk factor for non-communicable diseases and premature mortality. Promoting physical activity among healthcare professionals is important, yet little research has examined this population in Iraq. Aim: to assess physical activity motivators and barriers to physical activity among health providers in Karbala City, Iraq. Methods: A cross-sectional study was conducted among 800 healthcare professionals from selected hospitals and primary care centers in Karbala using validated questionnaires on physical activity (IPAQ), motivation (SMS-28), and barriers. Physical activity levels, motivations, and barriers were analyzed overall and by socio-demographics. Results: Approximately one-third (33.6%) were classified as physically inactive. No significant differences existed across gender, age groups, or type of healthcare staff. Key motivators were intrinsic factors like accomplishment, experience stimulation and knowledge. Top barriers were fear of injury, lack of skill, and social influences. Conclusion: High rates of physical inactivity among healthcare professionals highlight the need for targeted workplace strategies, leveraging intrinsic motivation and addressing barriers around skills, environment and safety concerns. Further research should explore causative factors and assess the impact of tailored interventions. Healthcare organizations play a pivotal role in prioritizing staff wellness to catalyze broader cultural shifts. Keywords: Karbala, health providors, physical activity, motivators, barriers